2009
DOI: 10.1063/1.3269924
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the regrowth surface of Si:P δ-layers toward vertically stacked three dimensional devices

Abstract: We investigate the surface quality of encapsulated Si:P δ-layers for the fabrication of multilayer devices with the potential to create architectures with sub 20 nm resolution in all three spatial dimensions. We use scanning tunneling microscopy to investigate how the dopant incorporation chemistry of the first active layer strongly affects the quality of the Si encapsulation which serves as the regrowth interface for the second active layer. Low temperature Hall measurements of the encapsulated layers indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 16 publications
2
54
0
Order By: Relevance
“…Low-temperature magnetotransport measurements confirm that all dopants are electrically activated after encapsulation [13], giving a maximal n s ¼ 2:4 Â 10 14 cm À2 . However, the presence of the PH x fragments, H and ejected Si on the surface result in limited Si adatom diffusion, reducing the quality of the homoepitaxial Si encapsulation with a corresponding increase in surface roughness [13,15,16]. Fig.…”
Section: Comparison Between Surfaces Of Single Dàlayersmentioning
confidence: 76%
See 2 more Smart Citations
“…Low-temperature magnetotransport measurements confirm that all dopants are electrically activated after encapsulation [13], giving a maximal n s ¼ 2:4 Â 10 14 cm À2 . However, the presence of the PH x fragments, H and ejected Si on the surface result in limited Si adatom diffusion, reducing the quality of the homoepitaxial Si encapsulation with a corresponding increase in surface roughness [13,15,16]. Fig.…”
Section: Comparison Between Surfaces Of Single Dàlayersmentioning
confidence: 76%
“…As a result, only a quarter of a monolayer of dopants remains after a 550 3 C anneal, giving n s ¼ 1:9 Â 10 14 cm À2 . However, the surface is atomically flat, providing a more ideal starting surface for the overgrowth of high quality, epitaxial silicon [13].…”
Section: Comparison Between Surfaces Of Single Dàlayersmentioning
confidence: 99%
See 1 more Smart Citation
“…Evolving Si quantum computing technologies are demanding epitaxial thin films with exceptionally flat and abrupt interfaces, ideally to the single-atomic-layer limit [1][2][3][4][5]. For a few leading qubit platforms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that epitaxial growth of silicon can occur at temperatures as low as room temperature [15] , and that Si film growth at room temperature up to several monolayers’ thickness has been successfully used as a locking layer to maintain ultra-sharp dopant profiles [16] . Electrical measurements by McKibbin et al [17] show 100% dopant activation at 250 °C encapsulation temperatures. Furthermore, it was shown that epitaxial encapsulation above 270 °C leads to dopant segregation with no improvement in the quality of overgrowth with a notable 50 % drop in carrier concentration.…”
Section: Introductionmentioning
confidence: 99%